Economic Significance of AI and Digitalization in the EU - Krushkina, Paolina (Research Papers, 2025)
The article explores the economic significance of artificial intelligence (AI) and digitization in the European Union (EU), focusing on their impact on productivity, competitiveness, and sustainability. In this context, certain challenges and opportunities associated with the implementation of AI and digital technologies are also identified. The main findings indicate that AI and digital technologies are crucial drivers of labor productivity growth. However, uneven infrastructure and a lack of skills may hinder the realization of their positive effects.